Das sereias ao canto do jaguar em “Meu tio o Iauaretê”, de Guimarães Rosa - Adriano, Geisy Nunes (2017)
This dissertation investigates the presence of the song of the sirens by Homer in "Meu tio o Iauaretê ", by Guimarães Rosa, using as theoretical reference the studies of Blanchot (2005), Oliveira (2008),), Agamben (2014) and Nogueira (2014), among others. In the wake of the interpretation of Blanchot, which traces an analogy between the song of the sirens and the literature making, every writer repeats the deed of Homeric’s character, since the narrative is an unpredictable and infinite searching movement, which makes present the navigation from the actual song to the imaginary song. We question whether there is a resumption of the song of the sirens in the studied narrative, with the goal of specifying how it happens and what its significance is, assuming that the jaguanhenhém song erupts from the threshold experience of metamorphosis between human and inhuman voice/song; portuguese, tupi and animal noise; articulated and unarticulated language. After analysis, we have come to the conclusion that this narrative stages the act of narrating itself, using a language between human-inhuman, in the process of enchantment, seduction and perdition of the triad author-narrator-reader